The cranial biomechanics and feeding performance of Homo floresiensis. Issue 5 (13th August 2021) - Cook, Rebecca W.; Vazzana, Antonino; Sorrentino, Rita; Benazzi, Stefano; Smith, Amanda L.; Strait, David S.; Ledogar, Justin A.
Abstract : Homo floresiensis is a small-bodied hominin from Flores, Indonesia, that exhibits plesiomorphic dentognathic features, including large premolars and a robust mandible, aspects of which have been considered australopith-like. However, relative to australopith species, H. floresiensis exhibits reduced molar size and a cranium with diminutive midfacial dimensions similar to those of later Homo, suggesting a reduction in the frequency of forceful biting behaviours. Our study uses finite-element analysis to examine the feeding biomechanics of the H. floresiensis cranium. We simulate premolar (P 3 ) and molar (M 2 ) biting in a finite-element model (FEM) of the H. floresiensis holotype cranium (LB1) and compare the mechanical results with FEMs of chimpanzees, modern humans and a sample of australopiths (MH1, Sts 5, OH5). With few exceptions, strain magnitudes in LB1 resemble elevated levels observed in modern Homo . Our analysis of LB1 suggests that H. floresiensis could produce bite forces with high mechanical efficiency, but was subject to tensile jaw joint reaction forces during molar biting, which perhaps constrained maximum postcanine bite force production. The inferred feeding biomechanics of H. floresiensis closely resemble modern humans, suggesting that this pattern may have been present in the last common ancestor of Homo sapiens and H. floresiensis .